THE EFFECT OF COAGULANT TYPE ON COLOR REDUCTION VARIATION PATTERN OF PEAT WATER IN COAGULATION-FLOCULATION PROCESS - Sutapa, Ignasius D. A.; Toruan, Reliana L. (LIPI Press, 2014)
Peat water has a wide variety of organic content; one of those is humic acid which looks like a seemingly brownish red color on the water. In a clean water system, the requirements that can be used for consumption islow intensity of color 15 TCU, while the peat water at Sala river was 540 TCU. Coagulation process has been known to affect the color reduction on peat water, but it is not yet known exactly how the optimum concentrationof coagulant. The aims of this study was to determine of PAC and alumunium sulphate effect to variation pattern of color reduction on peat water coagulation process, so that the optimum coagulant dosage, precipitation time and efficiency would be found out. The method used in the coagulation process was jar test. Based on this research, PAC and Aluminum sulphate optimum dosis were 180 ppm and 160 ppm, respectively. By such a dose, the color of the peat water can be reduced which is shown by the intensity of the color variations pattern. The efficiency of PAC within reduced peat water color was 99.63% (540 ppm to 2 ppm) and cost required was Rp 1800/day for 1 m3. Meanwhile, the efficiency of Alum was 95.37% (540 ppm to 22 ppm) and cost required was Rp 640/day for 1 m3. The use of PAC is considered more efficient and profitable than that of Alum, because using Alum needs peat water pH neutralization, and then it hikes the cost of peat water treatment. So, PAC is recommended on the scale of peat water treatment plant.